DETERMINAN FAKTOR PERKAWINAN ANAK (STUDI KASUS KECAMATAN LIMBOTO KABUPATEN GORONTALO) (Preventif : Jurnal Kesehatan Masyarakat, 2024)
Child marriage refers to the intimate union of a man and women under 19 years of age as a legal family. Gorontalo province is ranked the 15th with child marriage cases, particulary in a women with a percentage 0f 13,20%. The figure is eight times higher than the national standar, which is 10,82% (statistics Indonesia, 2020). Problem statement in this research is how the description of determinant of child marriage in Limboto Subdistrict, Gorontalo District. This research aims at gaining a description of the determinant of child marriage in Limboto Subdistrict, Gorontalo District. This type of research is a descriptive survey with a population of 219 married women aged